Ο Κονδυλάκης και το χρονογράφημα. - Σκοπετέας, Σταύρος Χ., 1908-1958 (Βασική βιβλιοθήκη / Αετός ;, 1956)
Ιωάννης Κονδυλάκης -- Οι πρόδρομοι του χρονογραφήματος: Κωνσταντίνος Πωπ -- Ειρηναίος Ασώπιος -- Αγγελος Βλάχος -- Χρονογράφοι: Εμμανουήλ Ροΐδης -- Στέφανος Γρανίτσας -- Αδωνις Κύρου -- Ιωάννης Κονδυλάκης -- Τίμος Παπαμιχαήλ -- Πλάτων Ροδοκανάκης -- Διονύσιος Φαραζουλής -- Πολύβιος Δημητρακόπουλος -- Ανδρέας Καρκαβίτσας -- Δημήτρης Ζαχαριάδης -- Τίμος Σταθόπουλος